Clinicians' Perceptions of Parent-Child Arts Therapy with Children with Autism Spectrum Disorders: The Milman Center Experience - Michal Bitan; Dafna Regev (MDPI AG, 2022)
Different types of arts offer a wide variety of modes of nonverbal communication and expressive tools for children with Autism Spectrum Disorders (ASD). The present study was designed to characterize therapists' perspectives on the implementation of a parent-child arts therapy model for children with ASD. Semi-structured interviews were conducted with 13 arts therapists who participated in the study. The thematic analysis (qualitative analysis) approach yielded seven themes: (1) Therapeutic goals. (2) Adjusting the therapeutic intervention. (3) The advantages of parent-child arts therapy. (4) Difficulties in parent-child arts therapy. (5) The unique contribution of the participants to parent-child arts therapy. (6) The different types of arts in the therapy room. (7) The arts therapists' assessment of the progress of therapy. The discussion focuses on the four central components of parent-child arts therapy room: the child in therapy, the parent, the arts therapist, and the creative arts.